Pondweeds of Florida - Christine Rohal; Laura Reynolds; Carrie Reinhardt Adams; Charles Martin (EDIS, 2020)
This new 9-page factsheet describes the defining characteristics of the eleven pondweed species that are present in Florida. It serves as a pondweed identification guide for aquatic habitat managers, lake monitors, conservationists, and plant enthusiasts, and it gives some context on each species’ life history and ecological role. Written by Christine Rohal, Laura Reynolds, Carrie Reinhardt Adams, and Charles Martin, and published by the UF/IFAS Department of Soil and Water Sciences. https://edis.ifas.ufl.edu/ss686